USA Track & Field elite athlete handbook 2010 (USA Track & Field, 2010)
This annual Elite Athlete Handbook is a tremendous resource for the professional athletes to get information about the sport, the organization and their place within USATF. The handbook covers many bases, from athlete support to travel information, from dealing with the media to drug testing changes, as well as a comprehensive calendar of upcoming 2010 events and directories for all aspects of the sport. Contents are, e. g.: - The presentation of the Sport Performance Department - Athlete Programs, e. g. USATF Performance Funding Programs/Services, High performance (HP) Programs/Services, United States Olympic Committee (USOC) Performance Funding Programs/Services, USATF Foundation Performance Funding Programs/Services, Elite Development Clubs or taxes, - Anti-Doping information, - Information around the USA 2010 National Teams and team staff, - Events/calendars - ....